40 Years With Abdul Kalam: Untold Story - Pillai, A. Sivathanu (New Delhi Pentagon Press, 2020)
Dr. Abdul Kalam, a great human being, established a unique place in the hearts of Indians with his admirable virtues and combined a simple lifestyle with strong willpower to envision an empowered nation. Without any ego, he could adapt himself to the situation to win over the person in front of him or would instantly become a captivating communicator to the audience. Every one, irrespective of age, position or religion, who met him at different occasions, celebrates him as a friend. As the eleventh President of India, he had totally changed the perception of India in the global arena. The author had the opportunity of working with this great soul closely for more than four decades and shared difficulties, failures and successes. This book discusses many of the interesting events, mostly the untold ones, during this journey, including those at ISRO, DRDO and BrahMos, and interactions with the corridors of power. Manufacturing is the key to economic prosperity and the chapter on Strategic Industries gives a complete insight on how India has steadily progressed in modern India. It was a long and unique journey for the author with the most appreciated true Indian, KALAM$1 (Bthe Brahmarishi.s
Keywords: History-India; Abdul Kalam